Negative electrode for all-solid-state battery and all-solid-state battery comprising same
Patent Information
- Application Number
- CN202580021167.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-06-12
- Filing Date
- 2025-06-13
- Publication Date
- 2026-10-20
AI Technical Summary
然而,当固体电解质材料被引入包含石墨的负极内部时,发生工艺变得复杂化并且电池能量密度降低的现象
[0029]根据本发明,通过在包含石墨作为负极活性材料的全固态电池用负极中引入多孔性碳层以促进锂离子移动,具有改善全固态电池用负极的离子电导率的效果。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority based on Korean Patent Application No. 10-2024-0078677, filed on June 18, 2024, and Korean Patent Application No. 10-2025-0076835, filed on June 12, 2025, the entire contents of which are incorporated herein by reference as a part of this specification. Technical Field
[0003] This invention relates to a negative electrode for an all-solid-state battery and an all-solid-state battery containing the negative electrode. Background Technology
[0004] Graphite, as a stable negative electrode material capable of high-rate charging, has been used in lithium-ion batteries (LIBs).
[0005] In batteries using conventional liquid electrolytes, the liquid electrolyte easily penetrates into the graphite-containing negative electrode, allowing lithium ions to easily transport between the graphite particles inside the negative electrode, resulting in excellent ionic conductivity inside the negative electrode.
[0006] However, the increasing demand for all-solid-state batteries uses solid electrolytes, which makes it difficult to ensure the ionic conductivity inside the negative electrode as when using liquid electrolytes.
[0007] To address this issue, techniques have been developed in all-solid-state batteries to introduce solid electrolyte materials into the graphite-containing negative electrode and utilize this solid electrolyte as a lithium-ion pathway, thereby ensuring the ionic conductivity within the negative electrode. However, when solid electrolyte materials are introduced into the graphite-containing negative electrode, the process becomes more complex and the battery energy density decreases. Furthermore, since the solid electrolyte is used as the lithium-ion transport pathway, it is not easy to ensure that the ionic conductivity reaches the same level as batteries using conventional liquid electrolytes. Moreover, side reactions may occur between the solid electrolyte and graphite, potentially leading to increased resistance.
[0008] Therefore, in order to use graphite as the negative electrode material for all-solid-state batteries, it is necessary to develop technologies that can prevent the increase of internal resistance of the negative electrode while improving the ionic conductivity of the negative electrode.
[0009] Existing technical documents
[0010] Patent documents
[0011] (Patent Document 1) Chinese Patent Gazette No. 117691060 Summary of the Invention
[0012] Technical issues
[0013] As a result of extensive research aimed at solving the aforementioned problems, the inventors have confirmed that by introducing a porous carbon layer into a graphite-containing negative electrode for all-solid-state batteries to promote lithium-ion movement, it is possible to prevent an increase in the resistance of the negative electrode for all-solid-state batteries while improving ionic conductivity.
[0014] Therefore, one object of the present invention is to provide a negative electrode for all-solid-state batteries that prevents the increase of resistance while improving ionic conductivity.
[0015] Furthermore, another object of the present invention is to provide an all-solid-state battery that includes a negative electrode for use in all-solid-state batteries, which prevents the increase of resistance while improving ionic conductivity.
[0016] Technical solution
[0017] To achieve the above objectives, the present invention provides a negative electrode for an all-solid-state battery, comprising: a negative electrode current collector; a negative electrode active material layer comprising graphite formed on one surface of the negative electrode current collector; and a porous carbon layer formed on one surface of the negative electrode active material layer.
[0018] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the porosity of the porous carbon layer is 30% to 60%.
[0019] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the thickness of the porous carbon layer is greater than 0 μm and less than 10 μm.
[0020] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the porous carbon layer comprises one or more carbon blacks selected from the group consisting of thermally cracked carbon black, acetylene black and Ketjen black.
[0021] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the negative electrode active material layer further comprises an adhesive.
[0022] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the adhesive comprises one or more selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), and carboxymethyl cellulose (CMC).
[0023] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the content of the binder is 1% to 5% by weight based on the total weight of the negative electrode active material layer.
[0024] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the active material layer of the negative electrode is SE-free.
[0025] In one embodiment of the present invention, the present invention provides a negative electrode for an all-solid-state battery, wherein the negative electrode current collector comprises stainless steel (SS), copper (Cu), nickel (Ni) or titanium (Ti).
[0026] The present invention also provides an all-solid-state battery comprising: a positive electrode; the negative electrode; and a solid electrolyte membrane sandwiched between the positive electrode and the negative electrode.
[0027] In one embodiment of the present invention, an all-solid-state battery is provided, wherein the solid electrolyte membrane comprises a sulfide-based solid electrolyte.
[0028] Invention Effects
[0029] According to the present invention, by introducing a porous carbon layer into an all-solid-state battery anode containing graphite as the negative electrode active material to promote lithium ion movement, the ionic conductivity of the all-solid-state battery anode is improved.
[0030] Furthermore, since no additional material is introduced to improve the ionic conductivity of the negative electrode for all-solid-state batteries as a lithium-ion transport path, it has the effect of preventing the increase in resistance caused by side reactions between the negative electrode active material and the additional material used as a lithium-ion transport path. Attached Figure Description
[0031] Figure 1 This is a graph showing the capacity retention rate of all-solid-state batteries manufactured in Examples 1, 2 and Comparative Example 1 according to the number of cycles.
[0032] Figure 2 This is a graph showing the coulombic efficiency of the all-solid-state batteries manufactured in Examples 1, 2 and Comparative Example 1 according to the number of cycles. Detailed Implementation
[0033] The invention will be described in more detail below to aid in understanding it.
[0034] The terms or words used in this specification and claims should not be construed as limited to their conventional or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical concept of the invention, based on the principle that the inventors can appropriately define the concepts of the terms in order to best describe their invention.
[0035] negative electrode for all-solid-state batteries
[0036] This invention relates to a negative electrode for all-solid-state batteries.
[0037] The negative electrode for all-solid-state batteries of the present invention comprises: a negative electrode current collector; a negative electrode active material layer containing graphite formed on one surface of the negative electrode current collector; and a porous carbon layer formed on one surface of the negative electrode active material layer.
[0038] In one embodiment of the present invention, the porosity of the porous carbon layer can be 30% to 60%.
[0039] The porous carbon layer can improve the ionic conductivity of the negative electrode by serving as a lithium ion pathway through the pores formed therein, thereby increasing oxygen saturation.
[0040] Furthermore, if the porosity of the porous carbon layer is less than 30%, the improvement in the ionic conductivity of the negative electrode may be minimal, while if it exceeds 60%, the mechanical properties of the negative electrode may deteriorate. Specifically, the porosity of the porous carbon layer can be above 30%, above 35%, or above 40%, and can be below 60%, below 55%, or below 50%.
[0041] In one embodiment of the present invention, the thickness of the porous carbon layer can be greater than 0 μm and less than 10 μm.
[0042] If the thickness of the porous carbon layer is 0 μm, its effect on improving the ionic conductivity of the negative electrode is minimal, and the battery's lifespan characteristics may deteriorate when applied to all-solid-state batteries. If it exceeds 10 μm, it may act as a resistor in the battery due to its excessive thickness. Specifically, the thickness of the porous carbon layer can be greater than 0 μm, greater than 1 μm, greater than 2 μm, or greater than 3 μm, and can be less than 10 μm, less than 9 μm, less than 8 μm, less than 7 μm, less than 6 μm, or less than 5 μm.
[0043] In one embodiment of the invention, the porous carbon layer may contain one or more carbon blacks selected from the group consisting of thermally cracked carbon black, acetylene black, and Ketjen black. However, there are no particular limitations on the type of carbon that may be contained in the porous carbon layer, as long as the carbon has good ionic conductivity, low reactivity with lithium ions, and good ion permeability.
[0044] Furthermore, the carbon may be doped with one or more elements selected from the group consisting of nitrogen, boron, and phosphorus. Due to the doping form of carbon, the effect of improving the ionic conductivity inside the negative electrode can be more significant.
[0045] In one embodiment of the invention, the negative electrode active material layer may further include an adhesive. The adhesive may be included to achieve bonding between the negative electrode active materials and between the negative electrode active material layer and the porous coating.
[0046] There are no particular limitations on the adhesive, as long as it can be used for the negative electrode of an all-solid-state battery. For example, the adhesive may contain one or more of the following: polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), and carboxymethyl cellulose (CMC). In addition, the adhesive may also comprise one or more of the following groups: styrene-butadiene rubber, acrylic-modified styrene-butadiene rubber, acrylonitrile copolymer, nitrile rubber (NBR), acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepoxychlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex rubber, acrylic resin, phenolic resin, epoxy resin, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate or ester, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, and polyurethane.
[0047] Furthermore, based on the total weight of the negative electrode active material layer, the content of the binder can be from 1% to 5% by weight. Specifically, the content of the binder can be more than 1% by weight, more than 1.5% by weight, or more than 2% by weight, and can be less than 5% by weight, less than 4.5% by weight, less than 4% by weight, less than 3.5% by weight, or less than 3% by weight. If the binder content is less than 1% by weight, the adhesion between the positive electrode active material and the positive electrode current collector may deteriorate; if it exceeds 5% by weight, although the adhesion is improved, the content of the negative electrode active material is correspondingly reduced, and the battery capacity may decrease.
[0048] In one embodiment of the present invention, the negative electrode active material layer comprises graphite as the negative electrode active material.
[0049] The graphite may include one or more selected from the group consisting of natural graphite and artificial graphite.
[0050] In addition to graphite, other negative electrode active materials may include: materials capable of reversibly inserting or deintercalating lithium ions (Li... + Materials that can react with lithium ions to reversibly form lithium-containing compounds, lithium metal, or lithium alloys.
[0051] Capable of reversibly inserting or de-inserting lithium ions (Li) + The material can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. It is capable of reacting with lithium ions (Li... +Materials that can reversibly form lithium-containing compounds through a reaction can be, for example, tin oxide, titanium nitride, or silicon. Lithium alloys can be, for example, alloys of lithium (Li) with metals selected from the group consisting of indium (In), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0052] Preferably, the negative electrode active material can be lithium metal or lithium-indium alloy (Li-In), specifically, it can be in the form of lithium metal, lithium film, lithium-indium alloy film, or powder.
[0053] In addition, silicon-based anode active materials may also be included as anode active materials.
[0054] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can range from 95% to 99.5% by weight. Specifically, the content of the negative electrode active material can be above 95% by weight or above 96% by weight, and can be below 99.5% by weight or below 99% by weight. If the content of the negative electrode active material is below 95% by weight, the performance of the battery may deteriorate; if it exceeds 99.5% by weight, the mass transfer resistance may increase.
[0055] In one embodiment of the present invention, the negative electrode active material layer may further comprise a conductive material. There are no particular limitations on the conductive material, as long as it can prevent side reactions in the internal environment of the all-solid-state battery, has excellent conductivity, and does not cause chemical changes within the battery.
[0056] For example, conductive carbon can be used as a conductive material. This conductive carbon can be used alone or in combination of two or more materials selected from: carbon materials having a crystal structure of graphene or graphite; conductive fibers such as carbon fibers and metal fibers; fluorinated carbon; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, but is not limited thereto.
[0057] Furthermore, based on the total weight of the negative electrode active material layer, the content of the conductive material can typically be from 0.5 wt% to 3 wt%. Specifically, the content of the conductive material can be more than 0.5 wt%, more than 1 wt%, or more than 1.5 wt%, and can be less than 3 wt%, less than 2.5 wt%, or less than 1 wt%. If the content of the conductive material is too low, less than 0.5 wt%, it may be difficult to expect an improvement in conductivity, or the electrochemical characteristics of the battery may deteriorate. If it is too high, exceeding 3 wt%, the amount of negative electrode active material becomes relatively small, and the capacity and energy density may deteriorate. There are no particular limitations on the method of introducing the conductive material into the negative electrode; conventional methods known in the art can be used, such as mixing with the negative electrode active material, coating, etc.
[0058] In one embodiment of the present invention, the negative electrode active material layer may be SE-free.
[0059] Typically, all-solid-state batteries include a solid electrolyte. Since the ionic conductivity is not as good as that of batteries containing liquid electrolytes, the solid electrolyte is introduced into the electrodes to compensate for this, allowing it to act as a lithium-ion transport pathway. However, the solid electrolyte, acting as a lithium-ion transport pathway, causes side reactions with the carbon materials contained in the electrodes and also acts as a resistor.
[0060] On the other hand, since the negative electrode of the all-solid-state battery of the present invention does not contain a solid electrolyte, the problem of increased resistance caused by the solid electrolyte can be prevented.
[0061] In one embodiment of the present invention, the negative electrode for an all-solid-state battery may further include a negative electrode current collector, one surface of which may be in contact with one surface of the negative electrode active material layer.
[0062] There are no particular restrictions on the negative electrode current collector, as long as it is conductive and does not cause chemical changes to the battery. For example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel, aluminum-cadmium alloys with surface treatments such as carbon, nickel, titanium, or silver. Furthermore, like the positive electrode current collector, the negative electrode current collector can be used in various forms with micro-uneven surfaces, such as films, sheets, foils, meshes, porous materials, foams, and non-woven fabrics.
[0063] Manufacturing method of negative electrode for all-solid-state battery
[0064] The present invention also relates to a method for manufacturing a negative electrode for an all-solid-state battery.
[0065] The method for manufacturing the negative electrode for an all-solid-state battery of the present invention includes: (S1) mixing graphite, which is a negative electrode active material, and a binder in a solvent to form a slurry for forming a negative electrode active material layer; (S2) coating the slurry for forming a negative electrode active material layer onto one surface of a negative electrode current collector to form a negative electrode active material layer; and (S3) coating a carbon slurry for forming a porous carbon layer onto one surface of the negative electrode active material layer to form a porous carbon layer.
[0066] The method for manufacturing the negative electrode for an all-solid-state battery according to the present invention will be described in more detail below for each step.
[0067] In one embodiment of the present invention, in step (S1), graphite, which serves as the negative electrode active material, and a binder are mixed in a solvent to form a slurry for forming a negative electrode active material layer. The types and amounts of the negative electrode active material and the binder are as described above.
[0068] The solvent is not particularly limited, as long as it is a solvent capable of forming a slurry for the negative electrode active material layer. For example, the solvent may be one or more selected from the group consisting of water, alcohol, acetone, dimethyl sulfoxide, formamide, and dimethylformamide. The alcohol may include one or more selected from the group consisting of methanol, ethanol, and isopropanol.
[0069] Furthermore, there are no particular restrictions on the concentration of the slurry used to form the negative electrode active material layer, as long as it is a concentration that allows for a smooth coating process. For example, the concentration of the slurry used to form the negative electrode active material layer can be between 5% and 30%. If the concentration of the slurry is below 5%, it is too thin and may not coat the substrate, instead flowing down. If it exceeds 30%, it is too thick, and coating may not be smooth. Specifically, the concentration of the slurry can be 5% or more, 10% or more, or 15% or more, and can be below 30% or 25%. In addition, the concentration can be based on the weight of solids, which can refer to materials contained in the slurry other than the solvent.
[0070] In one embodiment of the present invention, in step (S2), the negative electrode active material layer can be formed by coating a negative electrode active material layer forming slurry onto a surface of the negative electrode current collector.
[0071] Furthermore, after coating the negative electrode current collector with a slurry for forming a negative electrode active material layer, the negative electrode active material layer can be formed through a drying process.
[0072] Furthermore, there are no particular limitations on the coating method, as long as it is a coating method that can be used in the art to form a coating. For example, the coating method may be selected from the group consisting of dip coating, spray coating, spin coating, die coating, gravure coating, microgravure coating, comma coating, and roll coating.
[0073] In addition, the drying temperature can be between 100°C and 150°C. If the drying temperature is below 100°C, the drying may not be sufficient to form the negative electrode active material layer, and if it exceeds 150°C, the negative electrode active material layer may deform, such as cracking.
[0074] In one embodiment of the present invention, in step (S3), a porous carbon layer can be formed by coating a porous carbon layer forming carbon slurry onto one surface of a negative electrode active material layer.
[0075] The carbon slurry for forming a porous carbon layer can be prepared by mixing carbon in a solvent. The solvent and slurry concentration used to prepare the carbon slurry can be the same as those used in step (S2) when preparing the slurry for forming the negative electrode active material layer.
[0076] In addition, the coating method can be the same as that described in step (S2) above.
[0077] After coating a porous carbon layer with a carbon slurry, the solvent evaporates during drying, creating pores inside and thus forming a porous carbon layer. The more carbon that is well dispersed as nanounits, the more uniform the porous structure can be formed.
[0078] All-solid-state batteries
[0079] The present invention also relates to an all-solid-state battery comprising a negative electrode for an all-solid-state battery.
[0080] The all-solid-state battery of the present invention comprises a positive electrode, a negative electrode, and a solid electrolyte membrane sandwiched between the positive and negative electrodes. The negative electrode refers to the negative electrode used in the above-mentioned all-solid-state battery.
[0081] In one embodiment of the present invention, the solid electrolyte membrane included in the all-solid-state battery may comprise a sulfide-based solid electrolyte. There are no particular limitations on the sulfide-based solid electrolyte, as long as it is a sulfur-containing solid electrolyte.
[0082] For example, sulfide solid electrolytes can be represented by the following chemical formula 1: <Chemical Formula 1> Li a M b S c X d In chemical formula 1, M is selected from P, Sn, Sb, As, and Ge; X is selected from Cl, Br, and I. 5 ≤ a ≤ 7.5, 0.5 < b ≤ 1.5, 4 < c ≤ 6, 0.5 < d ≤ 2.
[0083] Furthermore, solid electrolytes can exist in an amorphous or crystalline state. Additionally, they can exist in a mixed state of amorphous and crystalline states.
[0084] Solid electrolyte membranes may also contain adhesives. Examples of adhesive materials include acrylonitrile butadiene rubber (NBR), styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene, and polyacrylic acid resins. The adhesive material may be the same as or different from the materials used in the adhesives constituting the positive and negative electrode active material layers.
[0085] In one embodiment of the present invention, the positive electrode included in the all-solid-state battery comprises a positive electrode active material layer, which may be formed on a surface of the positive electrode current collector.
[0086] The positive electrode active material layer comprises a positive electrode active material, a conductive material, and a binder. Additionally, the positive electrode active material layer may also contain a solid electrolyte.
[0087] Furthermore, there are no particular restrictions on the positive electrode active material, as long as it is a material capable of reversibly absorbing and releasing lithium ions, such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and Li[Ni] x Co y Mn z M v O2 (where M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1, x+y+z+v=1), Li (Li a M b-a-b' M' b' )O 2-c A c (In the formula, 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2, 0≤c≤0.2; M includes Mn and one or more selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' is one or more selected from the group consisting of Al, Mg and B; A is one or more selected from the group consisting of P, F, S and N) and other layered compounds or compounds substituted with one or more transition metals; such as the chemical formula Li 1+y Mn 2-y Lithium manganese oxides such as O4 (where y is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2 compounds; lithium copper oxides (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and LiNi oxides. 1-y M yNickel-site lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Lithium manganese composite oxides represented by O2 (where M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced by an alkaline earth metal ion; disulfide compounds; Fe2(MoO4)3, etc., but not limited to these.
[0088] Furthermore, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can range from 60% to 90% by weight. Specifically, the content of the positive electrode active material can be 60% by weight, 65% or more, or 70% or more, and can be less than 90% by weight, 85% or less, or 80% by weight. If the content of the positive electrode active material is less than 60% by weight, the battery performance may deteriorate; if it exceeds 90% by weight, the mass transfer resistance may increase.
[0089] Furthermore, there are no particular limitations on the conductive material, as long as it can prevent side reactions in the internal environment of the all-solid-state battery and has excellent conductivity without causing chemical changes in the battery. Graphite or conductive carbon can typically be used. For example, the following materials can be used alone or in mixtures of two or more: graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, Ketjen black, Denka black, thermal cracking carbon black, channel black, furnace black, lamp black, and summer carbon black; carbon materials with a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; fluorinated carbon; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, but are not necessarily limited to these. Preferably, the conductive material may include vapor-grown carbon fiber (VGCF).
[0090] Based on the total weight of the positive electrode active material layer, the content of conductive material can typically range from 1% to 10% by weight. Specifically, the content of conductive material can be more than 1% by weight, more than 2% by weight, or more than 3% by weight, and can be less than 10% by weight, less than 9% by weight, or less than 8% by weight. If the content of conductive material is too low, less than 1% by weight, it may be difficult to expect an improvement in conductivity, or the electrochemical characteristics of the battery may deteriorate. Conversely, if it is too high, exceeding 10% by weight, the amount of positive electrode active material becomes relatively small, and the capacity and energy density may deteriorate. There are no particular limitations on the method of introducing conductive material into the positive electrode; conventional methods known in the art can be used, such as mixing with the positive electrode active material, coating, etc.
[0091] In addition, the adhesive is a component that assists in bonding the positive electrode active material to the conductive material and to the current collector, and may include, selected from, styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, and polyepoxyethylene. The adhesive comprises one or more of the following: alcohols, polyphosphazenes, polyacrylonitrile, polystyrene, latex, acrylic resins, phenolic resins, epoxy resins, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyesters, polyamides, polyethers, polyimides, polycarboxylic acid esters or salts, polycarboxylic acids, polyacrylic acid, polyacrylates, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene. Preferably, the adhesive may include polytetrafluoroethylene (PTFE).
[0092] Furthermore, based on the total weight of the positive electrode active material layer, the binder content can be from 1% to 10% by weight. Specifically, the binder content can be more than 1% by weight, more than 2% by weight, or more than 3% by weight, and can be less than 10% by weight, less than 9% by weight, or less than 8% by weight. If the binder content is less than 1% by weight, the adhesion between the positive electrode active material and the positive electrode current collector may deteriorate. If it exceeds 10% by weight, although the adhesion is improved, the content of the positive electrode active material is reduced accordingly, and the battery capacity may decrease.
[0093] Furthermore, the solid electrolyte can be a sulfide-based solid electrolyte. There are no particular limitations on the sulfide-based solid electrolyte, as long as it is a sulfur-containing solid electrolyte.
[0094] Based on the total weight of the positive electrode active material layer, the content of the solid electrolyte can be from 5% to 20% by weight. When the content of the solid electrolyte is within this range, the ionic conductivity can be improved. Specifically, the content of the solid electrolyte can be 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, or 10% or more, and can be less than 20% by weight, less than 19% by weight, less than 18% by weight, less than 17% by weight, less than 16% by weight, less than 15% by weight, less than 14% by weight, less than 13% by weight, or less than 12% by weight.
[0095] In addition, the positive current collector supports the positive active material layer and plays a role in transferring electrons between the external wire and the positive active material layer.
[0096] There are no particular restrictions on the positive electrode current collector, as long as it has high electronic conductivity and does not cause chemical changes in the all-solid-state battery. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, copper or stainless steel, aluminum-cadmium alloys with surface treatments such as carbon, nickel, or silver can be used as the positive electrode current collector.
[0097] To enhance the bonding force with the positive electrode active material layer, the positive electrode current collector can have a fine uneven structure on its surface, or adopt a three-dimensional porous structure. Therefore, the positive electrode current collector can take various forms such as membranes, sheets, foils, sieves, meshes, porous bodies, foams, and non-woven fabrics.
[0098] The aforementioned positive electrode can be prepared using conventional methods. Specifically, it can be prepared by coating a positive electrode active material layer forming composition, prepared by mixing positive electrode active material, conductive material, and binder in an organic solvent, onto a positive electrode current collector and drying it. Optionally, the current collector can be compressed to increase the electrode density. In this case, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, binder, and conductive material and is easily evaporable. Examples of such solvents include acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropanol.
[0099] Battery Module
[0100] The present invention also relates to a battery module comprising the all-solid-state battery as a unit cell, a battery pack comprising the battery module, and an apparatus comprising the battery pack as a power source.
[0101] Specific examples of the device include, but are not limited to: power tools that move by receiving power from an electric motor; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs); electric two-wheelers, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; energy storage systems; and energy storage systems.
[0102] Example
[0103] Preferred embodiments will be provided below to aid in understanding the invention. However, the following examples are merely illustrative of the invention. It will be apparent to those skilled in the art that various changes and modifications can be made within the scope and concept of the invention, and these changes and modifications naturally fall within the scope of the appended claims.
[0104] Example 1
[0105] (1) Manufacturing of negative electrodes for all-solid-state batteries
[0106] Natural graphite, used as the negative electrode active material, and polyvinylidene fluoride (PVdF), used as a binder, were mixed at a weight ratio of 97.5:2.5. Then, a slurry for forming the negative electrode active material layer, mixed in an ethanol solvent, was coated onto stainless steel (SS), used as the negative electrode current collector. The mixture was subsequently dried at 100°C to form the negative electrode active material layer. At this point, the concentration of the slurry for forming the negative electrode active material layer was 20% based on the weight of the solids. The solids refer to natural graphite and the binder.
[0107] Next, carbon black (Asahi carbon Co., CB78) was mixed in an ethanol solvent to prepare a slurry for forming a porous carbon layer. At this time, the concentration of the slurry for forming a porous carbon layer was set to 20%. The slurry for forming a porous carbon layer was coated onto the negative electrode active material layer and dried at 120°C to form a porous carbon layer with a thickness of 9 μm.
[0108] (2) Manufacturing of positive electrodes for all-solid-state batteries
[0109] 80% by weight of LiNi was used as the positive electrode active material. 0.8 Co 0.1 Mn 0.1 O2 (NCM811), 11% by weight of Li6PS5Cl as a solid electrolyte, 5% by weight of conductive material (vapor-grown carbon fiber, VGCF) and 4% by weight of binder polymer (polyvinylidene fluoride, PVDF) were mixed, and then N-methylpyrrolidone solvent was added to further prepare the positive electrode active material slurry, taking viscosity into consideration.
[0110] The prepared positive electrode active material slurry was coated onto an aluminum current collector with a thickness of 20 μm, and then vacuum dried at 120℃ for 24 hours to prepare the positive electrode.
[0111] (3) Manufacturing of solid electrolyte membranes
[0112] A slurry for forming a sulfide-based solid electrolyte membrane was prepared by mixing Li6PS5Cl, which has a sulfide-silver-germanium mineral structure, as a sulfide-based solid electrolyte, and acrylonitrile rubber (NBR) as a binder in a weight ratio of 90:10 in butyrate ester as a non-polar solvent, so that the solid content is 50% by weight.
[0113] A slurry for forming a sulfide-based solid electrolyte membrane is coated onto a PET (polyethylene terephthalate) substrate using a doctor blade coater, and then vacuum dried at 70°C for 5 hours to form a sulfide-based solid electrolyte membrane.
[0114] (4) Manufacturing of all-solid-state batteries
[0115] A solid-state battery was prepared by sandwiching a solid electrolyte membrane between the negative and positive electrodes of the all-solid-state battery prepared above.
[0116] Example 2
[0117] Except for making the thickness of the porous carbon layer 15 μm, the same method as in Example 1 was performed.
[0118] Comparative Example 1
[0119] Except that a porous carbon layer was not formed when manufacturing the negative electrode for all-solid-state batteries, the same method as in Example 1 was performed.
[0120] Experiment Example 1: Battery Performance Measurement
[0121] The all-solid-state batteries manufactured in the examples and comparative examples were activated twice at 0.05C in a charge-discharge apparatus, and then their rate performance was observed using a scheme involving discharge up to the maximum value of 1C. Specifically, the rate performance was observed using the following scheme: two cycles of 0.05C CC / CV (constant current / constant voltage) charging and 0.05C CC (constant current) discharging, followed by maintaining a 0.1C CC / CV charging process while simultaneously performing CC discharges at 0.1C / 0.2C / 0.33C / 0.5C / 1C.
[0122] Figure 1 This is a graph showing the capacity retention rate of all-solid-state batteries manufactured in Examples 1, 2 and Comparative Example 1 according to the number of cycles.
[0123] See Figure 1 As can be seen, in Comparative Example 1, where no carbon layer was coated on the negative electrode active material layer, the cycle retention rate rapidly deteriorated after 12 to 13 cycles.
[0124] Furthermore, it can be seen that the cycle retention rate of Example 2 is slightly lower than that of Example 1. This can be attributed to the fact that the thickness of the porous carbon layer in Example 2 is thicker than that in Example 1.
[0125] Figure 2 This is a graph showing the coulombic efficiency of the all-solid-state batteries manufactured in Examples 1, 2 and Comparative Example 1 according to the number of cycles.
[0126] See Figure 2 The results show that in Comparative Example 1, where no carbon layer was coated on the negative electrode active material layer, the coulombic efficiency rapidly deteriorated within 15 cycles as the charge capacity increased, leading to a short circuit. This can be presumed to be due to insufficient assurance of ion transport paths in the negative electrode.
[0127] Furthermore, it can be seen that the cycle retention rate and coulombic efficiency of the battery influence each other.
[0128] Although the invention has been described with reference to limited embodiments and figures, it is not limited thereto. It is obvious to those skilled in the art that various modifications and variations can be made within the technical spirit of the invention and within the equivalent scope of the claims.
Claims
1. A negative electrode for an all-solid-state battery, comprising: Negative current collector; A graphite-containing negative electrode active material layer formed on one surface of the negative electrode current collector; and A porous carbon layer is formed on one surface of the negative electrode active material layer.
2. The negative electrode for an all-solid-state battery as described in claim 1, wherein, The porosity of the porous carbon layer is 30% to 60%.
3. The negative electrode for an all-solid-state battery as described in claim 1, wherein, The thickness of the porous carbon layer is greater than 0 μm and less than 10 μm.
4. The negative electrode for an all-solid-state battery as described in claim 1, wherein, The porous carbon layer comprises one or more carbon blacks selected from the group consisting of thermally cracked carbon black, acetylene black, and Ketjen black.
5. The negative electrode for an all-solid-state battery as described in claim 1, wherein, The negative electrode active material layer also includes an adhesive.
6. The negative electrode for an all-solid-state battery as described in claim 5, wherein, The adhesive comprises one or more of the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), and carboxymethyl cellulose (CMC).
7. The negative electrode for an all-solid-state battery as described in claim 5, wherein, The content of the adhesive is from 1% to 5% by weight, based on the total weight of the negative electrode active material layer.
8. The negative electrode for an all-solid-state battery as described in claim 1, wherein, The negative electrode active material layer is SE-Free.
9. The negative electrode for an all-solid-state battery as described in claim 1, wherein, The negative current collector contains stainless steel (SS), copper (Cu), nickel (Ni), or titanium (Ti).
10. An all-solid-state battery, comprising: positive electrode; The negative electrode as described in claim 1; and A solid electrolyte membrane sandwiched between the positive electrode and the negative electrode.
11. The all-solid-state battery as claimed in claim 10, wherein, The solid electrolyte membrane contains a sulfide-based solid electrolyte.
Citation Information
Patent Citations
Detachable loafers
KR1020240078677A
System for provides efficiency driving guide through energy usage prediction
KR1020250076835A